(untitled) (Research, Society and Development, 2022)
Introduction: Levonorgestrel is a contraceptive drug that is mainly used over-the-counter in Brazil, and the lack of knowledge of women about the morning-after pill is also a factor that induces the exaggerated consumption of this method. The irrational use, in a frequent way, in addition to increasing the opportunities for the occurrence of already known adverse reactions, and decreasing the effectiveness of emergency contraception, can also lead to health risks. Objective: The present study aimed to carry out an analysis of the current existing literature regarding the risks of indiscriminate use of emergency contraceptives (EC). Materials and methods: For this purpose, the following electronic databases were carried out: NCBI/PubMed Virtual Library, LILACS – Bireme (Latin American and Caribbean Literature on Health Sciences) and Google Scholar and SciELO (Scientific Electronic Lirary Online), with the year of publication between 2012 and 2022. Results: The results obtained from the search in the consulted databases resulted in 74 articles, where 30 were pre-selected, and after reading in full, 12 articles were defined to compose the study. Discussion: Thus, it can be observed that although EC is considered a safe method, little is known about its mechanism of action and its effects on the female body. Conclusion: The role of nurses as health educators, being duly trained for the educational function, ensuring good quality information and the availability of alternatives.